Sthenelais limicola ... - Barnich, Ruth; Haaren, Ton Van (Zenodo, 2021)
Sthenelais limicola (Ehlers, 1864) (emended) Figs 1–2 Sigalion limicola Ehlers, 1864: 120. Sthenelais leiolepis Claparède, 1868: 406–409, pl. 4 fig. 3, pl. 6 fig. 1 (description sufficient; see also Barnich & Fiege 2003). Sthenelais haddoni McIntosh, 1897a: 403. Syn. nov. Sthenelais filamentosus Ditlevsen, 1917: 50, pl. 4 fig. 6, pl. 5 fig. 9. Syn. nov. ? Aphrodita arcta Dalyell, 1853: 170, pl. 24 fig. 14 (see McIntosh 1900; however, description insufficient). Sthenelais limicola – Pruvot & Racovitza 1895: 473, pl. 20 figs 122–123. — McIntosh 1900: 417, pl. 29 fig. 3, pl. 31 fig. 6, pl. 34 figs 9–11, pl. 42 figs 1–4. — Fauvel 1923: 113, fig. 42a–g. — Chambers 1985: 29–30, figs 1b, 2a, 15b–c, 21b–e. — Hartmann-Schröder 1996: 83 fig. 28. — Chambers & Muir 1997: 158, fig. 51. — Barnich & Fiege 2003: 132, fig. 65. — Gil 2011: 947. — Núñez et al. 2015: 244, fig. 98. Diagnosis Dorsal cirri absent on segment 3. Ventral body surface smooth. Outer elytral margin with irregular extensions (anterior ... : Published as part of Barnich, Ruth & Haaren, Ton Van, 2021, Revision of Sthenelais Kinberg, 1856, Fimbriosthenelais Pettibone, 1971 and Eusthenelais McIntosh, 1876 (Polychaeta, Sigalionidae) in the Northeast Atlantic, pp. 138-171 in European Journal of Taxonomy 740 on pages 145-148, DOI: 10.5852/ejt.2021.740.1287, http://zenodo.org/record/4649646 ...